Correlation Study of Organizational Culture with Environmental Performance of Small and Medium Enterprises in East Java, Indonesia - Purwanto, Fajar; Riyadi, Slamet; Ardiana, I Dewa Ketut Raka (International Journal of Scientific Research and Management (IJSRM), 2023)
The development of the business world today has triggered the emergence of micro, small and medium businesses that exist in the global economy and offer a variety of food and beverage products that vary based on the market. This indirectly triggers competition between business actors and has the potential to trigger environmental damage if not taken seriously. This also increases the risk of environmental damage around the business location and environmental damage throughout Indonesia. Some efforts that can be made to overcome this are by implementing organizational culture at the business level. This study aims to analyse the relationship between organizational culture and environmental performance within small and medium enterprises in East Java. The type of research used is causal research. The research sample was as many as 400 respondents who fulfilled the research criteria. For the sampling technique, probability sampling was used with a cluster random sampling approach. The variables in this study are organizational culture and environmental performance. The data collection technique used in this study was a questionnaire. The data analysis method used in this research is descriptive statistics, classical assumption test, path analysis, F test and coefficient of determination test. Based on the results of the study, it can be concluded that there is no correlation between organizational culture and environmental performance in small and medium enterprises in the East Java region with a critical ratio (CR) value of 1.011 (smaller than 1,96) and a significance value (p-value) of 0,312